AKTIVITAS ANTIBAKTERI EKSTRAK DAUN NANGKA KUNING (VINCETOXICUM VILLOSUM (BLUME) KUNTZE) TERHADAP BAKTERI ENTEROCOCCUS FAECALIS DAN PSEUDOMONAS AERUGINOSA - Oktoviani, Oktoviani; Pertiwi, R; Notriawan, D.; Putri, B. A. N.; Karlina, Y. D. (Politeknik Kesehatan Kemenkes Bengkulu, 2021)
Nangka kuning leaves (Vincetoxicum villosum Blume) are widely used by the community as a traditional medicine but research on nangka kuning leaves is still very limited so that it has great potential for the development of herbal medicine. This study used two bacteria representing gram-positive and gram-negative groups. From the gram-positive group, one of the most common bacteria that can cause disease is the Enterococcus faecalis. Then from the gram-negative group used Pseudomonas aeruginosa which is the most common cause of opportunistic infections in hospitalized patients. To test the antibacterial activity of the ethanol extract, bacteria were divided into 8 groups, namely the positive control group with chloramphenicol, the negative control group with 10% Dimethyl Sulfoxide (DMSO) solvent, and 6 treatment groups using 12.5% ​​ethanol extract; 15%; 17.5%; 20%; 22.5%; 25%. Bacterial culture was carried out using media and incubated for 24 hours at 37oC. Enterococcus faecalis bacteria used Trypticase Soy Both (TSB) media and Pseudomonas Aeruginosa bacteria used Trypticase Soy Agar (TSA) media. The optimal inhibition for Enterococcus faecalis bacteria is in the ethanol extract of Vincetoxicum Villosum Blume with a concentration of 25% and for Pseudomonas aeruginosa is the ethanol extract of Vincetoxicum Villosum Blume with a concentration of 15%.